KEBUTUHAN SPIRITUALITAS LANSIA DENGAN PENYAKIT KRONIS YANG HIDUP SENDIRI DI WILAYAH KERJA DINAS KESEHATAN KABUPATEN MOJOKERTO - Arief Andriyanto; Siti Hidayatul Badriyah; Valen Fridolin Simak (Universitas Sam Ratulangi, 2024)
Background: Spirituality helps elderly people adapt to changes within themselves. The process of healing chronic diseases in the elderly requires good spirituality. However, in reality, there are still many elderly people who have low spirituality. Objective: This research aims to describe the spiritual needs of elderly people with chronic illnesses who live alone in the Mojokerto District Health Service Work Area. Method: Observational descriptive research design. The sample consisted of 210 elderly people who were taken by purposive sampling in the Mojokerto Regency Health Service Work Area. The spiritual needs questionnaire instrument adopted by researchers from Ummah (2017) to identify spiritual needs consists of 25 questions. Results: The results of the study showed that the spiritual needs of elderly people with chronic illnesses were on average in the sufficient category. Conclusion: Respondents who have spiritual needs are good because they are good at connecting with other people, nature/the environment, and God. Health workers at Posyandu activities provide information about the importance of spirituality and how to increase spirituality in the elderly by participating in religious activities already carried out by the elderly in their daily lives. Keywords: Chronic Disease; Elderly; Spirituality needs